Impact of Minnesota's "Profile of Learning" - Avery, Patricia G.; Beach, Richard; Coler, Jodiann (Education Policy Analysis Archives, 2003)
In 1990, the Minnesota State Board of Education declared its intention to develop a "results-oriented graduation requirement" based on student achievement as opposed to the usual credit/course completion requirement. In addition to a traditional test of basic skills, the state began developing the Profile of Learning, a set of performance-based standards grounded in a constructivist educational philosophy, an approach that differs from the content-based standards found in many states. The Profile was controversial from its inception. Conservatives characterized the Profile as too process- oriented and as lacking subject-matter content; teachers reported that the Profile required a significant amount of additional teacher preparation time; and parents, who were not adequately informed about the Profile, questioned the purpose of the Profile. Teachers were frustrated with the confusing and sometimes contradictory directions they received from the Minnesota Department of Children, Families, and Learning charged with implementing the Profile. In 2000-2001, we surveyed and interviewed selected secondary English and social studies teachers in the state about their perceptions of the Profile’s impact on teaching and learning. Among the positive perceptions was an increase in students’ higher order thinking, students’ understanding of criteria for quality work, and teachers conversations with one another about instructional issues. Increased teacher preparation time and decreased enjoyment of teaching were among the negative perceptions. Teachers also experienced difficulty adopting performance assessment techniques. When teachers believed they received effective preparation and adequate resources for working with the Profile, they were much more likely to report beneficial effects in terms of teaching and learning. The majority of teachers, however, rated their preparation and resources as "fair" or "poor." Results are discussed in terms of school and instructional change.